SPECIALISED FINANCIAL COMPANIES AS AN INSTRUMENT OF ASSET SECURITISATION - Anna I. Navalikhina (Russian Studies in Law and Politics)
The relevance of the topic is due to the increasing influence of Specialized Financial Companies in connection with the constant development of the investment market and the increasing need of society in innovative products, taking into account the lack of research in the Russian science and expert community. It should also be noted that Specialized Financial Societies are becoming an increasingly interesting instrument both abroad and in Russian corporate law, especially in view of the forthcoming “tax reform” in 2025.